Elevated temperature and CO2 have positive effects on the growth and survival of larval Australasian snapper. (October 2020) - McMahon, Shannon J.; Parsons, Darren M.; Donelson, Jennifer M.; Pether, Steve M.J.; Munday, Philip L.
Abstract: Rising water temperature and increased uptake of CO2 by the ocean are predicted to have widespread impacts on marine species. However, the effects are likely to vary, depending on a species' sensitivity and the geographical location of the population. Here, we investigated the potential effects of elevated temperature and p CO2 on larval growth and survival in a New Zealand population of the Australasian snapper, Chrysophyrs auratus . Eggs and larvae were reared in a fully cross-factored experiment (18 °C and 22 °C/ p CO2 440 and 1040 μatm) to 16 days post hatch (dph). Morphologies at 1 dph and 16 dph were significantly affected by temperature, but not CO2 . At 1dph, larvae at 22 °C were longer (7%) and had larger muscle depth at vent (14%), but had reduced yolk (65%) and oil globule size (16%). Reduced yolk reserves in recently hatched larvae suggests higher metabolic demands in warmer water. At 16 dph, larvae at elevated temperature were longer (12%) and muscle depth at vent was larger (64%). Conversely, survival was primarily affected by CO2 rather than temperature. Survivorship at 1 dph and 16 dph was 24% and 54% higher, respectively, under elevated CO2 compared with ambient conditions. Elevated temperature increased survival (24%) at 1 dph, but not at 16 dph. These results suggest that projected climate change scenarios may have an overall positive effect on early life history growth and survival in this population of C. auratus . This could benefit recruitment success, but needs to be weighed against negative effects of elevated CO2 on metabolic rates and swimming performance observed in other studies on the same population. Highlights: Larval Snapper were positively affected by projected end of century temperature and  p CO2  from fertilization to 16dph. Elevated temperature increased the size of larvae, however high p CO2 had no effect. High p CO2 significantly increased survival at 16 days post-hatch, but elevated temperature had no effect. Some species and populations of marine fish exhibit positive effects from projected environmental change.